Cellulose nanocrystal zero-valent iron nanocomposites for groundwater remediation. Issue 6 (26th April 2017) - Bossa, Nathan; Carpenter, Alexis Wells; Kumar, Naresh; de Lannoy, Charles-François; Wiesner, Mark
Abstract : Use of crystal nanocellulose to stabilize nano-ZVI has tremendous potential to improve the capability and applicability of nano-ZVI based subsurface remediation systems in an environmentally sustainable way. Abstract : Zero-valent iron nanoparticles (nano-ZVIs) have been widely studied for in situ remediation of groundwater and other environmental matrices. Nano-ZVI particle mobility and reactivity are still the main impediments in achieving efficient in situ groundwater remediation. Compared to the nano-ZVI "coating" strategy, nano-ZVI stabilization on supporting material allows direct contact with the contaminant, reduces the electron path from the nano-ZVI to the target contaminant and increases nano-ZVI reactivity. Herein, we report the synthesis of nano-ZVI stabilized by cellulose nanocrystal (CNC) rigid nanomaterials (CNC-nano-ZVI; Fe/CNC = 1 w/w) with two different CNC functional surfaces (–OH and –COOH) using a classic sodium borohydride synthesis pathway. The final nanocomposites were thoroughly characterized and the reactivity of CNC-nano-ZVIs was assessed by their methyl orange (MO) dye degradation potential. The mobility of nanocomposites was determined in (sand/glass bead) porous media by utilizing a series of flowthrough transport column experiments. The synthesized CNC-nano-ZVI provided a stable colloidal suspension and demonstrated high mobility in porous media with an attachment efficiency ( α ) value of less than 0.23. In addition, reactivity toward MO increased up to 25% compared to bare ZVI. The use of CNC as a delivery vehicle shows promising potential to further improve the capability and applicability of nano-ZVI for in situ groundwater remediation and can spur advancements in CNC-based nanocomposites for their application in environmental remediation.